Relationship Between Usage of Eye Prosthetics with Anxiety: A Literature Review - Gina Sonia Fensilia Yolanda (Sriwijaya Journal of Ophthalmology, 2021)
Eyes are not only a functioning organ for vision but also an integral part of one’s self esteem if it functions normally. A loss of this function with or without disfigurement will give a significant impact on someone’s mental well being and if not identified and managed quickly it will deranged into mental illness. While eye prosthetics help, it is not without flaws. One of the most prominent mental disease related to these cases are anxiety. This journal serves as a review for the updated evidence for this particular topic especially the risks involved in developing said mental illness so modulation of intervention could be given to patients with eye prosthetics.